Reduced exercise capacity is associated with left ventricular systolic dysfunction in long‐term survivors of allogeneic hematopoietic stem‐cell transplantation. Issue 1 (5th July 2022) - Massey, Richard John; Myrdal, Ole Henrik; Diep, Phoi Phoi; Burman, Marta Maria; Brinch, Lorentz; Gullestad, Lars Lysgaard; Ruud, Ellen; Aakhus, Svend; Beitnes, Jan Otto
Abstract: Purpose: Exercise intolerance is a common complication in survivors of allogeneic hematopoietic stem‐cell transplantation (allo‐HSCT). The aim of this study was to determine if cardiac function measured with echocardiography is associated with exercise capacity measured with cardio‐pulmonary exercise tests in long‐term survivors treated in their youth with allo‐HSCT. Methods: The study included 96 patients, of which 54.2% were female, aged 34.9 ± 11.6 years and 17.7 ± 9.3 years after allo‐HSCT. Reduced exercise capacity was defined as <85% of predicted‐peak oxygen uptake (VO2peak ). Linear regression was used in the prediction of VO2peak (ml/kg/min). Receiver operating characteristic evaluated the accuracy of predicting reduced exercise capacity. Results: VO2peak was 36.2 ± 7.7 ml/kg/min and 43 (44.8%) had reduced exercise capacity. Left ventricular ejection fraction was 55.4 ± 5.9% and global longitudinal strain (GLS) was −17.6% ± 2.0%. Left and right ventricular functions were significantly lower in survivors with reduced exercise capacity. Increased body mass index, lower physical activity score, reduced pulmonary function (by forced expiratory volume in 1‐s) and reduced left ventricular systolic function (by GLS) were significant independent predictors for reduced VO2peak . GLS was superior to other echocardiographical indices for identifying reduced exercise capacity (area under curve = 0.64, p = 0.014). Conclusions: Left ventricular systolic dysfunction measured by GLS is associated with reduced exercise capacity in long‐term allo‐HSCT survivors. Abstract : Exercise intolerance is a common complication in long‐term survivors of allogeneic hematopoietic stem‐cell transplantation. In this study, we found reduced oxygen uptake (VO2peak ) by cardio‐pulmonary exercise tests to be associated with left ventricular systolic dysfunction by echocardiography. In particular, global longitudinal strain was found to have superior ability to predict VO2peak compared to other echocardiographical parameters.